Unveiling the effects of nonviolent communication training on youth empathy - Aistė Batūraitė-Bunka; Margarita Jurevičienė; Gert Skoczowsky-Danielsen (Social Welfare: Interdisciplinary Approach, 2024)
Nonviolent communication (NVC) is a model of communication approach, a method, a process, a mindset and a way of life, and was developed by Marshal Rosenberg. NVC offers tools that support the principle of nonviolence and empathic communication. Empathy can be important in promoting pro-environmental behavior (Kansky & Massarani, 2022), and the lack of empathy has been associated with antisocial behavior and reoffending (Bazemore & Stinchcomb, 2004).